2014
DOI: 10.2460/ajvr.75.7.626
|View full text |Cite
|
Sign up to set email alerts
|

Canine stifle joint biomechanics associated with tibial plateau leveling osteotomy predicted by use of a computer model

Abstract: In the model, stifle joint biomechanics were partially improved after TPLO, compared with CrCL-deficient stifle joint biomechanics, but TPLO did not fully restore CrCL-intact stifle joint biomechanics. Overrotation of the tibial fragment negatively influenced stifle joint biomechanics by increasing caudal tibial translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Biomechanical studies evaluating TPLO and TTA have used various methods to generate cranial tibial thrust and have shown that both techniques result in active stability of the CCL deficient stifle . All of these in vitro studies reported that both TPLO and TTA effectively stopped the cranial translation of the tibia relative to the femur in the CCL deficient stifle by neutralizing the cranial component of the joint reaction force.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical studies evaluating TPLO and TTA have used various methods to generate cranial tibial thrust and have shown that both techniques result in active stability of the CCL deficient stifle . All of these in vitro studies reported that both TPLO and TTA effectively stopped the cranial translation of the tibia relative to the femur in the CCL deficient stifle by neutralizing the cranial component of the joint reaction force.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found cranial tibial translation may be either reduced, neutralized, or converted to caudal tibial translation following TTA . However, if cranial tibial translation is converted to caudal tibial translation, the caudal cruciate ligament may experience increased strain or loading and be predisposed to injury . Increased loads placed on the patellar ligament may lead to thickening of the ligament, but the relevance of this change remains unknown .…”
mentioning
confidence: 99%
“…Canine pelvic limb computer simulation models with anatomically accurate geometry and active muscle forces have been used to investigate ligament loading patterns and stifle kinematics in the intact stifle, CrCL‐deficient stifle, and tibial plateau leveling osteotomy‐treated stifle during the stance phase of gait . Computer models have also been used to predict the sensitivity of biomechanical outcomes to variation of anatomic and surgical parameters .…”
mentioning
confidence: 99%
See 2 more Smart Citations